Clinical Outcomes of Trans-Sacral Epiduroscopic Laser Decompression (SELD) in Patients with Lumbar Disc Herniation - Seong Son; Sang Gu Lee; Yong Ahn; Woo Kyung Kim (Pain Research and Management)
Objective. Nowadays, trans-sacral epiduroscopic laser decompression (SELD) using slender epiduroscopy and laser is one of the preferred options for minimally invasive treatment in lumbar disc diseases. However, SELD is still in the initial stages of the global field of spine surgery, and the clinical outcomes in patients with lumbar disc herniation are not established yet. Therefore, the authors investigated patients undergoing SELD to report the clinical results. Methods. Between November 2015 and November 2018, a total of 82 patients who underwent single-level SELD for lumbar disc herniation with a minimum follow-up of 6.0 months were enrolled. A retrospective review of clinical data was conducted. Clinical outcomes were evaluated using the visual analogue scale (VAS) for low back and leg pain and Odom’s criteria. Also, surgical outcomes, including complications and symptom recurrences, and radiological outcomes were analyzed. Results. Low back pain and leg pain as determined by the VAS improved from an average of 5.43 ± 1.73 and 6.10 ± 1.67 to 2.80 ± 1.43 and 3.58 ± 2.08 at the final follow-up (p<0.001). According to Odom’s criteria, the success rate defined as excellent or good results at the final follow-up was 58.5%. There were no surgery-related complications such as neurologic deficits, infection, or epidural hematomas, except for transient mild paralysis in 3 patients and procedure-related nuchal pain in 2 patients. The rate of additional procedures was 17.0% (6 patients received revision surgery and 8 patients received an additional nerve block) during the follow-up. Conclusion. Our findings showed that SELD for lumbar herniated disc disease achieved less favorable clinical outcomes compared with those of previous studies. Further study is needed to clarify the influencing factors on the clinical outcomes of SELD.